Reconfiguring Public Accountability in Digital Service Innovation: A Case Study of Palapa Mojo in Mojokerto - Warsito, Lazuwardy 'Alam Qalby; Amalia, Virdha Melinda; Wardiyanto, Bintoro (Jurnal Review Politik, 2026)
This study analyzes the accountability of the digital public service innovation “Palapa Mojo” through four dimensions: legality and honesty, process, program and policy. The aim is to identify the extent to which this integrated application applies the principles of accountability in public services. The method used is a literature study by collecting and analyzing data from various secondary sources related to the development and implementation of Palapa Mojo. The results show that Palapa Mojo comprehensively reflects the seven doctrines of NPM, such as professional management, explicit performance standards, focus on output, functional decentralization, competitive spirit, adoption of private management styles, and discipline in the use of resources. In terms of accountability, this innovation fulfills the four dimensions of public accountability: law, process, program, and policy. Palapa Mojo has proven to be an efficient and accountable public service innovation, successfully transforming services through digital integration, self-managed budget savings, increased access and transparency, and becoming a best practice model.